Fluffy hair microspheres for dry hair spray, preparation method and oil-absorbing particles

By using HDI/trimethylolhexyllactone crosslinked polymer in dry hair spray to wrap hollow corn starch, depositing zinc oxide layer on the polymer film, and then wrapping it with lauroyl lysine to form a special spherical structure of fluffy microspheres, it solves the residual, low transparency, poor oil absorption effect and potential threats to scalp health of existing dry hair spray products, achieving higher oil absorption value, transparency and smoothness, and providing ultraviolet protection.

CN119097575BActive Publication Date: 2025-04-04YANGRUN TECH (GUANGDONG) CO LTD

Patent Information

Application Number
CN202411220935.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2025-04-04
Estimated Expiration
2044-09-02

AI Technical Summary

Technical Problem

The existing dry hair spray products have residuals due to large particle sizes of starch and silica, low transparency, poor oil absorption effect, potential threats to scalp health and poor user experience.

Method used

The HDI/trimethylolhexyllactone crosslinked polymer is used to tightly wrap hollow corn starch, and a zinc oxide layer is deposited on the polymer film, and then wrapped with lauroyl lysine as the outermost layer to form a special spherical structure of a fluffy microsphere.

Benefits of technology

Improves the oil absorption, transparency and smoothness of the dry hair spray, provides UV protection, reduces residue, improves user experience and protects scalp health.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119097575B_ABST
    Figure CN119097575B_ABST
Patent Text Reader

Abstract

The present application relates to the field of dry hair spray, and more specifically, to a kind of fluffy hair microspheres used in dry hair spray, a preparation method and oil-absorbing particles. A kind of fluffy hair microspheres used in dry hair spray, comprising: hollow corn starch, HDI / trimethylol hexyl lactone cross-linked polymer, zinc oxide, and lauroyl lysine; the preparation method thereof is: stirring the hollow corn starch, spraying the HDI / trimethylol hexyl lactone cross-linked polymer solution on the surface of the hollow corn starch to obtain a wrapped hollow corn starch; spraying zinc oxide on the wrapped hollow corn starch to make it adhere to the surface of the wrapped hollow corn starch to form a deposit to obtain a deposited hollow corn starch; spraying lauroyl lysine on the deposited hollow corn starch to obtain fluffy hair microspheres used in dry hair spray. The present application provides a fluffy hair microsphere material with high transparency and UV protection function to replace or optimize traditional ingredients, which becomes the key to improving the performance and market competitiveness of dry hair spray products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of dry hair spray, and more specifically, to a kind of fluffy hair microspheres used in dry hair spray, a preparation method and oil-absorbing particles. Background Art

[0002] Most of the dry hair sprays on the market use starch and silica as their main ingredients. Although they meet the basic needs of oil absorption and oil removal to a certain extent, their inherent defects significantly limit their market acceptance and use effect. The main defects are as follows:

[0003] (1) The particle size of starch and silica particles is relatively large, which directly leads to obvious residue on the hair after use, reduces the transparency of the product, makes the hair prone to whitening, and affects the overall aesthetics. This shortcoming is particularly significant for modern consumers who pursue natural and traceless effects.

[0004] (2) Although starch and silica have a certain oil absorption capacity, their oil absorption value is not outstanding, and a higher addition amount is often required to achieve the ideal oil absorption effect. However, a high addition amount not only increases the cost, but may also cause side effects such as dry hair and easy tangling, affecting the consumer's experience.

[0005] (3) Starch, as a natural polysaccharide, is a good culture medium for bacterial growth. Starch has poor hydrophobicity and can easily promote bacterial growth if it stays on the scalp for a long time, leading to sensitive problems such as scalp itching and redness, posing a potential threat to scalp health.

[0006] (4) The powder mixed with starch and silica is not smooth and has low smoothness. The powder is easy to fall off or rub unevenly during use, which reduces user satisfaction. In addition, hands need to be cleaned frequently after touching the powder, which also increases the inconvenience of use.

[0007] (6) Traditional dry hair sprays mainly focus on oil absorption and lack the ability to fully protect hair, such as protecting against UV damage. As consumers’ demands for the functions of hair care products diversify, such single-function products can no longer meet market demand.

[0008] Therefore, developing a highly transparent, UV-resistant fluffy microsphere material to replace or optimize traditional ingredients has become the key to improving the performance and market competitiveness of dry hair spray products. Summary of the invention

[0009] In order to solve the above problems, the present application provides a fluffy hair microsphere used in dry hair spray, a preparation method and oil-absorbing particles.

[0010] In the first aspect, the present application provides a type of fluffy hair microspheres for use in dry hair spray, which adopts the following technical solution: a type of fluffy hair microspheres for use in dry hair spray, comprising the following raw materials, in parts by mass: 5-20 parts of hollow corn starch, 35-60 parts of HDI / trimethylol hexyllactone cross-linked polymer, 0.1-5 parts of zinc oxide, and 1-10 parts of lauroyl lysine.

[0011] Preferably, the following raw materials are included in parts by mass: 10-15 parts of hollow corn starch, 45-50 parts of HDI / trimethylol hexyl lactone cross-linked polymer, 0.5-1.5 parts of zinc oxide, and 0.5-1.5 parts of lauroyl lysine.

[0012] Preferably, the particle size of the hollow corn starch is 2.5-4 μm.

[0013] Preferably, the particle size of the fluffy microspheres used in the dry hair spray is 4-8 μm.

[0014] The fluffy hair microspheres provided in the present application are a special spherical structure in which hollow corn starch is tightly wrapped by HDI / trimethylol hexyl lactone crosslinked polymer, a zinc oxide layer is effectively deposited on the polymer film, and lauroyl lysine is used as the outermost layer. This special structure is applied in dry hair spray to improve various properties.

[0015] The introduction of the zinc oxide layer gives the dry hair spray a highly effective UV protection capability, effectively blocking direct UV radiation to the hair and reducing UV-induced hair damage. Lauroyl lysine, as the outermost wrapping material, not only enhances the skin-friendliness of the fluffy microspheres, but also significantly improves the smoothness after use, making the hair feel smoother and enhancing the consumer experience. Of course, the above effects are not the performance of zinc oxide or lauroyl lysine alone, but need to be based on the special structure of the fluffy microspheres to work well.

[0016] The dry hair spray made by the physical combination of fluffy microspheres and silica has a lower repose angle and a higher water contact angle. The dry hair spray can be spread more evenly on the hair and is easy to shake off from the hair to avoid residue and keep the hair fresh and tidy.

[0017] The specially structured fluffy microspheres have a higher oil absorption value, so that the dry hair spray can achieve the ideal degreasing effect with a small amount of use, which is both economical and environmentally friendly. In addition, the fluffy microspheres have and can maintain a high degree of transparency, especially in the preferred particle size range of 4-8μm, the transparency is higher. The specially structured fluffy microspheres can, on the one hand, reduce the amount of dry hair spray using the fluffy microspheres; on the other hand, the fluffy microspheres have a higher transparency and are not easy to leave obvious white marks on the hair, maintaining the natural color and luster of the hair and improving the overall aesthetics.

[0018] In summary, the fluffy microspheres provided in the present application are applied to dry hair spray, which can significantly improve the comprehensive performance of the dry hair spray, bring better usage experience to consumers, and have significant market value and social benefits.

[0019] In a second aspect, the present application provides a method for preparing fluffy microspheres for use in dry hair spray, using the following technical solution:

[0020] A method for preparing fluffy microspheres for dry hair spray comprises the following steps:

[0021] Step 1: Stir the hollow corn starch at 1000-2000 r / min and 60-80° C., spray the HDI / trimethylol hexyl lactone crosslinked polymer solution on the surface of the hollow corn starch, and keep stirring for 20-45 minutes to obtain the wrapped hollow corn starch;

[0022] Step 2: maintaining 1000-2000r / min, setting the temperature to 85-95°C, spraying zinc oxide onto the wrapped hollow corn starch to make it adhere to the surface of the wrapped hollow corn starch to form a deposit, and continuously stirring for 20-45min to obtain deposited hollow corn starch;

[0023] Step 3: Set the speed to 1500-2500 r / min, the temperature to 85-95° C., spray lauroyl lysine onto the deposited hollow corn starch, and continue stirring for 45-75 minutes to obtain fluffy microspheres for dry hair spray.

[0024] By adopting the above technical solution, the timing of adding raw materials and conditions such as temperature and rotation speed are strictly limited to achieve full reaction.

[0025] Under the conditions of 1000-2000r / min and 60-80℃, HDI / trimethylol hexyl lactone cross-linked polymer forms a complete and tough coating on the surface of hollow corn starch, providing a good foundation for the subsequent zinc oxide deposition, so that zinc oxide can be more evenly and firmly deposited on the surface of the wrapped hollow corn starch, thereby exerting a significantly excellent sunscreen performance. Finally, lauroyl lysine is used to wrap the deposited hollow corn starch to enhance the hydrophobicity of the obtained fluffy microspheres, which have a better smoothness.

[0026] It should be noted that step 1 needs to be strictly controlled at a temperature of 60-80°C. If the temperature is too high, the hollow corn starch will easily age and turn yellow, and its toughness will deteriorate under long-term high temperature, which will have a great impact on subsequent performance.

[0027] Preferably, step 1 is carried out under the conditions of 1500 r / min and 70°C.

[0028] Preferably, in step 1, the HDI / trimethylol hexyl lactone crosslinked polymer solution is sprayed in small amounts multiple times.

[0029] Preferably, in step 2, zinc oxide is sprayed in small amounts multiple times.

[0030] In the present application, zinc oxide needs to be evenly deposited on the surface of the hollow corn starch. Since the amount of zinc oxide added in the present application is not much, if it cannot be evenly deposited, it cannot achieve a good sunscreen effect. Therefore, under strictly limited conditions, further use of a small amount of multiple spraying methods can help zinc oxide to be evenly deposited, and the effect is better.

[0031] Preferably, in step 3, lauroyl lysine is sprayed in small amounts multiple times.

[0032] Preferably, the preparation method of hollow corn starch comprises the following steps:

[0033] Step a, inoculating the starch-degrading bacterial strain into a starch agar medium, activating it, and culturing it at a constant temperature of 25-30° C. for 168-360 hours to obtain an acclimated strain;

[0034] Step b, adding corn starch to deionized water to prepare a 20% corn starch suspension;

[0035] Step c, inoculating the domesticated mixed strain into corn starch suspension, adjusting the suspension to a temperature of 30-40° C. and a pH of 6.0-8.0, standing for 48-72 hours, washing and drying, and obtaining hollow corn starch.

[0036] In a third aspect, the present application provides an oil-absorbing particle, which adopts the following technical solution:

[0037] The invention discloses oil-absorbing particles, comprising fluffy microspheres and silica for use in dry hair spray.

[0038] According to the mass fraction of the oil-absorbing particles, the fluffy microspheres used in the dry hair spray are 50-70 parts, and the silica is 30-50 parts.

[0039] During the mixing process of silica and the fluffy microspheres used in dry hair spray, part of the silica and the fluffy microspheres used in dry hair spray will produce adsorption and bonding effects due to polarity, making the structure of the oil-absorbing particles more stable, thereby giving full play to the performance of the fluffy microspheres used in dry hair spray.

[0040] In summary, this application has the following beneficial effects:

[0041] 1. The porous hollow corn starch with modified surface has a higher oil absorption value when combined with silica to prepare dry hair spray, which is 20% higher than the previous product, and also enhances the smoothness.

[0042] 2. The particle size of the fluffy microspheres is in the optimal range of 4-8μm. They absorb oil quickly, do not appear white, have high uniformity, and the hollow corn starch with modified surface is combined with silica to show higher transparency.

[0043] 3. The fluffy microspheres have the function of resisting ultraviolet rays, effectively protecting the hair from damage and truly protecting the health of the hair from the source. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 This is an electron microscope image of the hollow corn starch of Example 1 of the present application.

[0045] Figure 2 This is an electron microscope image of the wrapped hollow corn starch in Example 1 of the present application.

[0046] Figure 3 This is an electron microscope image of the deposited hollow corn starch in Example 1 of the present application.

[0047] Figure 4 This is an electron microscope image of the fluffy microspheres used in dry hair spray according to Example 1 of the present application.

[0048] Figure 5 This is the test result of Example 1, ST-7028A and CR-930 in the black and white grid hiding power cardboard test of Test 2 of this application.

[0049] Figure 6 This is the test result of Example 1 in the spectrophotometer light transmittance comparison test of Test 2 of this application. The left side is the oil-absorbing particles of Example 1, and the right side is the test slurry formed by dissolving Example 1 with anhydrous ethanol.

[0050] Figure 7 This is the test result of Example 1 in the spectrophotometer light transmittance comparison test of Test 2 of this application. The left side shows the situation of pushing the oil-absorbing particles of Example 1 on a glass sheet with a wire rod coater, and the right side shows the situation of the test slurry of Example 1 being scraped and coated into a film. DETAILED DESCRIPTION

[0051] The present application is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0052] The raw materials used in the following examples and comparative examples are all commercially available products.

[0053] Preparation Example

[0054] Preparation Example 1

[0055] The preparation method of hollow corn starch comprises the following steps:

[0056] Step a: inoculate the starch-degrading bacterial strain into a starch agar medium, activate it, and culture it at a constant temperature of 25-30° C. for 168-360 hours to obtain an acclimated strain.

[0057] The starch-degrading bacterial strain (BNCC132483) was purchased from Guangdong Microbiological Collection Center.

[0058] Specifically, 0.75 g of the strain was added to 75 mL of starch agar medium, and cultured in a constant temperature shaker at 27.5° C. at a speed of 200 r / min for 18 hours, and then placed in a constant temperature incubator at 27.5° C. for 264 hours until the absorbance in the culture medium was 0.25.

[0059] Step b: Add corn starch to deionized water to prepare a 20% corn starch suspension.

[0060] Specifically, 20 g of corn starch was added into 100 mL of water, and the mixture was stirred to dissolve, and the mixture was mixed and stirred to make the corn starch evenly dissolved to obtain a 20% corn starch suspension.

[0061] Step c: inoculating the domesticated strain into a corn starch suspension, adjusting the suspension to a temperature of 30-40° C. and a pH of 6.0-8.0, standing the suspension for 48-72 hours, washing and drying the suspension to obtain hollow corn starch.

[0062] Specifically, 75 mL of 20% corn starch suspension was taken, and 10 mL of the domesticated strain was added to the 20% corn starch suspension to obtain a mixed solution.

[0063] The mixed solution was then heated to 35° C. using a constant temperature water bath, and the pH of the suspension was adjusted to 7.0 using a 0.1 mol / L hydrochloric acid solution and a 0.1 mol / L sodium hydroxide solution, and the suspension was allowed to stand for 60 hours.

[0064] After the reaction is completed, the mixture is washed with deionized water and then dried in an oven at 60° C. to obtain hollow corn starch.

[0065] Example

[0066] Example 1

[0067] A kind of fluffy hair microspheres used in dry hair spray comprises the following components: 10kg of hollow corn starch, 45kg of HDI / trimethylol hexyl lactone cross-linked polymer, 0.5kg of zinc oxide and 0.5kg of lauroyl lysine.

[0068] The present application also provides a method for preparing fluffy microspheres for use in dry hair spray, comprising the following steps:

[0069] Step 1: Put the hollow corn starch (refer to the electron microscope picture Figure 1 ) was added to the reactor, the speed of the reactor was adjusted to 1500r / min, and the temperature was maintained at 70°C. The HDI / trimethylol hexyl lactone cross-linked polymer solution was sprayed into the reactor through a spray head, and stirring was maintained for 30 minutes to obtain hollow corn starch (the electron microscope structure is referenced Figure 2 ).

[0070] In this process, the HDI / trimethylol hexyl lactone cross-linked polymer fully reacts with the hollow corn starch to form a coating layer on the surface.

[0071] During this period, the HDI / trimethylol hexyllactone cross-linked polymer solution is sprayed in 3-4 times. The spraying amount each time can fluctuate but should not differ too much, and spray in small amounts multiple times.

[0072] The HDI / trimethylol hexyl lactone crosslinked polymer solution is a commercially available solvent-based product, and the solid content of the HDI / trimethylol hexyl lactone crosslinked polymer is 45%.

[0073] The hollow corn starch was prepared by the method of Preparation Example 1, and the hollow corn starch with a particle size in the range of 2.5-4 μm was selected.

[0074] Step 2: Maintain 1500r / min and raise the temperature to 90°C. Spray zinc oxide powder into the reactor several times in small amounts to make it adhere to the surface of the hollow corn starch to form a deposit. Continue stirring for 30 minutes to obtain the deposited hollow corn starch (see electron microscope image for details). Figure 3 ).

[0075] Multiple small amounts can be three times, and each time you can distribute them evenly.

[0076] Step 3: Increase the speed to 2000r / min, maintain the temperature at 90°C, spray lauroyl lysine into the reactor several times in small amounts, and continue stirring for 60 minutes.

[0077] The material is discharged and sieved through a vibrating screen to obtain fluffy microspheres with a particle size of 4-8 μm for use in dry hair spray (see electron microscope image for details). Figure 4 ).

[0078] Multiple small amounts can be three times, and each time you can distribute them evenly.

[0079] This embodiment also discloses an oil-absorbing particle, comprising 56 kg of fluffy microspheres used in dry hair spray and 44 kg of silica.

[0080] The fluffy microspheres used in the dry hair spray and the silica can be mixed evenly by physical mixing.

[0081] Example 2

[0082] A kind of fluffy microspheres used in dry hair spray, which is different from Example 1 in that it comprises the following components: 20kg hollow corn starch, 35kg HDI / trimethylol hexyl lactone cross-linked polymer, 5kg zinc oxide, and 10kg lauroyl lysine.

[0083] A method for preparing fluffy microspheres for dry hair spray, which is different from Example 1 in that it comprises the following steps:

[0084] Step 1: Add the hollow corn starch into the reactor, adjust the speed of the reactor to 1000 r / min, and keep the temperature at 80° C. Spray the HDI / trimethylol hexyl lactone crosslinked polymer solution into the reactor through a spray head, and keep stirring for 20 minutes to obtain the wrapped hollow corn starch.

[0085] In this process, the HDI / trimethylol hexyl lactone cross-linked polymer fully reacts with the hollow corn starch to form a coating layer on the surface.

[0086] During this period, the HDI / trimethylol hexyllactone cross-linked polymer solution is sprayed in 3-4 times. The spraying amount each time can fluctuate but should not differ too much, and spray in small amounts multiple times.

[0087] The HDI / trimethylol hexyl lactone crosslinked polymer solution is a commercially available solvent-based product, and the solid content of the HDI / trimethylol hexyl lactone crosslinked polymer is 45%.

[0088] The hollow corn starch was prepared by the method of Preparation Example 1, and the hollow corn starch with a particle size in the range of 2.5-4 μm was selected.

[0089] Step 2: Maintain 1000r / min and raise the temperature to 95°C. Spray zinc oxide powder into the reactor in small amounts several times to make it adhere to the surface of the hollow corn starch to form a deposit, and continue stirring for 20 minutes to obtain the deposited hollow corn starch.

[0090] Multiple small amounts can be three times, and each time you can distribute them evenly.

[0091] Step 3: Increase the speed to 1500r / min, maintain the temperature at 95°C, spray lauroyl lysine into the reactor several times in small amounts, and continue stirring for 45 minutes.

[0092] The material is discharged and sieved through a vibrating screen to obtain fluffy hair microspheres with a particle size in the range of 4-8 μm for use in dry hair spray.

[0093] Multiple small amounts can be three times, and each time you can distribute them evenly.

[0094] This embodiment also discloses an oil-absorbing particle, comprising 70 kg of fluffy microspheres used in dry hair spray and 30 kg of silica.

[0095] The fluffy microspheres used in the dry hair spray and the silica can be mixed evenly by physical mixing.

[0096] Example 3

[0097] A kind of fluffy microspheres used in dry hair spray, which is different from Example 1 in that it comprises the following components: 5kg hollow corn starch, 60kg HDI / trimethylol hexyl lactone crosslinked polymer, 0.1kg zinc oxide, and 1kg lauroyl lysine.

[0098] A method for preparing fluffy microspheres for dry hair spray, which is different from Example 1 in that it comprises the following steps:

[0099] Step 1: Add the hollow corn starch into the reactor, adjust the speed of the reactor to 2000 r / min, and keep the temperature at 60° C. Spray the HDI / trimethylol hexyl lactone crosslinked polymer solution into the reactor through a spray head, and keep stirring for 45 minutes to obtain the wrapped hollow corn starch.

[0100] In this process, the HDI / trimethylol hexyl lactone cross-linked polymer fully reacts with the hollow corn starch to form a coating layer on the surface.

[0101] During this period, the HDI / trimethylol hexyllactone cross-linked polymer solution is sprayed in 3-4 times. The spraying amount each time can fluctuate but should not differ too much, and spray in small amounts multiple times.

[0102] The HDI / trimethylol hexyl lactone crosslinked polymer solution is a commercially available solvent-based product, and the solid content of the HDI / trimethylol hexyl lactone crosslinked polymer is 45%.

[0103] The hollow corn starch was prepared by the method of Preparation Example 1, and the hollow corn starch with a particle size in the range of 2.5-4 μm was selected.

[0104] Step 2: Maintain 2000r / min and raise the temperature to 85°C. Spray zinc oxide powder into the reactor in small amounts several times to make it adhere to the surface of the hollow corn starch to form a deposit, and continue stirring for 45 minutes to obtain the deposited hollow corn starch.

[0105] Multiple small amounts can be three times, and each time you can distribute them evenly.

[0106] Step 3: Increase the speed to 2500r / min, maintain the temperature at 85°C, spray lauroyl lysine into the reactor several times in small amounts, and continue stirring for 75 minutes.

[0107] The material is discharged and sieved through a vibrating screen to obtain fluffy hair microspheres with a particle size in the range of 4-8 μm for use in dry hair spray.

[0108] Multiple small amounts can be three times, and each time you can distribute them evenly.

[0109] This embodiment also discloses an oil-absorbing particle, comprising 66.1 kg of fluffy microspheres used in dry hair spray and 33.9 kg of silica.

[0110] The fluffy microspheres used in the dry hair spray and the silica can be mixed evenly by physical mixing.

[0111] Example 4

[0112] A kind of fluffy microspheres used in dry hair spray, which is different from Example 1 in that it comprises the following components: 15kg hollow corn starch, 50kg HDI / trimethylol hexyl lactone crosslinked polymer, 1.5kg zinc oxide, and 1.5kg lauroyl lysine.

[0113] The preparation method of the fluffy microspheres for dry hair spray is the same as that in Example 1 and will not be described in detail here.

[0114] This embodiment also discloses an oil-absorbing particle, comprising 68 kg of fluffy microspheres used in dry hair spray and 32 kg of silica.

[0115] The fluffy microspheres used in the dry hair spray and the silica can be mixed evenly by physical mixing.

[0116] Table 1

[0117]

[0118] Comparative Example

[0119] Comparative Example 1

[0120] A method for preparing fluffy microspheres for dry hair spray, which is different from Example 1 in that it includes the following steps: Step 1: Add hollow corn starch into a reactor, adjust the speed of the reactor to 1500 r / min, and keep the temperature at 90° C. Spray the HDI / trimethylol hexyl lactone crosslinked polymer solution into the reactor through a spray head, keep stirring for 30 minutes, and obtain the hollow corn starch.

[0121] In this process, the HDI / trimethylol hexyl lactone cross-linked polymer fully reacts with the hollow corn starch to form a coating layer on the surface.

[0122] During this period, the HDI / trimethylol hexyllactone cross-linked polymer solution is sprayed in 3-4 times. The spraying amount each time can fluctuate but should not differ too much, and spray in small amounts multiple times.

[0123] The HDI / trimethylol hexyl lactone crosslinked polymer solution is a commercially available solvent-based product, and the solid content of the HDI / trimethylol hexyl lactone crosslinked polymer is 45%.

[0124] The particle size of hollow corn starch is selected to be in the range of 2.5-4μm.

[0125] Step 2: Maintain 1500r / min and raise the temperature to 90°C. Spray zinc oxide powder into the reactor in small amounts several times to make it adhere to the surface of the hollow corn starch to form a deposit, and continue stirring for 30 minutes to obtain the deposited hollow corn starch.

[0126] Multiple small amounts can be three times, and each time you can distribute them evenly.

[0127] Step 3: Increase the speed to 2000r / min, maintain the temperature at 90°C, spray lauroyl lysine into the reactor several times in small amounts, and continue stirring for 60 minutes.

[0128] The material is discharged and sieved through a vibrating screen to obtain fluffy hair microspheres with a particle size in the range of 4-8 μm for use in dry hair spray.

[0129] Multiple small amounts can be three times, and each time you can distribute them evenly.

[0130] Comparative Example 2

[0131] A method for preparing fluffy microspheres for dry hair spray, which is different from Example 1 in that it comprises the following steps:

[0132] Step 1: Add the hollow corn starch into the reactor, adjust the speed of the reactor to 500 r / min, and keep the temperature at 70° C. Spray the HDI / trimethylol hexyl lactone crosslinked polymer solution into the reactor through a spray head, and keep stirring for 30 minutes to obtain the wrapped hollow corn starch.

[0133] In this process, the HDI / trimethylol hexyl lactone cross-linked polymer fully reacts with the hollow corn starch to form a coating layer on the surface.

[0134] During this period, the HDI / trimethylol hexyllactone cross-linked polymer solution is sprayed in 3-4 times. The spraying amount each time can fluctuate but should not differ too much, and spray in small amounts multiple times.

[0135] The HDI / trimethylol hexyl lactone crosslinked polymer solution is a commercially available solvent-based product, and the solid content of the HDI / trimethylol hexyl lactone crosslinked polymer is 45%.

[0136] The particle size of hollow corn starch is selected to be in the range of 2.5-4μm.

[0137] Step 2: Maintain 1500r / min and raise the temperature to 90°C. Spray zinc oxide powder into the reactor in small amounts several times to make it adhere to the surface of the hollow corn starch to form a deposit, and continue stirring for 30 minutes to obtain the deposited hollow corn starch.

[0138] Multiple small amounts can be three times, and each time you can distribute them evenly.

[0139] Step 3: Increase the speed to 2000r / min, maintain the temperature at 90°C, spray lauroyl lysine into the reactor several times in small amounts, and continue stirring for 60 minutes.

[0140] The material is discharged and sieved through a vibrating screen to obtain fluffy hair microspheres with a particle size in the range of 4-8 μm for use in dry hair spray.

[0141] Multiple small amounts can be three times, and each time you can distribute them evenly.

[0142] Performance testing

[0143] Test 1:

[0144] The angle of repose, bulk density, water contact angle and oil absorption value of the oil absorbing particles of Examples 1-2 and Comparative Examples 1-2 were tested, and the data were recorded in Table 1.

[0145] Angle of repose: refer to GBT 16913-2008 "Dust properties test method".

[0146] Bulk density: refer to GB / T 31057.1-2014 "Physical properties test of granular materials Part 1: Measurement of bulk density".

[0147] Water contact angle: Use a powder contact angle meter to test the water contact angle of the sample.

[0148] Oil absorption value: Use German automatic oil absorption instrument and reagent grade refined linseed oil to test the oil absorption value of the sample to be tested.

[0149] Meaning of detection indicators:

[0150] The lower the angle of repose, the higher the fluidity, the better the ductility and the better the performance.

[0151] The lower the bulk density, the higher the product fluffiness and the better the product performance.

[0152] The larger the water contact angle, the higher the hydrophobicity and the better the product performance.

[0153] The higher the oil absorption value, the better the oil absorption effect and the better the product performance.

[0154] Table 1

[0155]

[0156] According to the test data in Table 1, Examples 1-2 are superior to Comparative Examples 1-2 and Competitor 1 in many aspects. The oil-absorbing particles of Examples 1-2 have better ductility, higher fluffiness, better hydrophobicity, and better oil absorption effect.

[0157] Test 2: Transparency

[0158] 1. Black and white grid hiding power cardboard: The oil-absorbing particles of Examples 1-4 and Comparative Examples 1-2 and Competitor 1-2 were dissolved in dicaprylyl carbonate at a ratio of 1:2 to form a test slurry. The test slurry was scraped onto a glass sheet with a wire rod coater to a film thickness of 10 μm. The test slurry was then compared with black and white grid hiding power cardboard and observed with the naked eye.

[0159] The scale is based on a score of 0-5. The closer to 5, the better the transparency. 0 represents the worst transparency, and 5 represents the best transparency.

[0160] The results are recorded in Table 2.

[0161] The test results of Example 1 (PG-9500T), Competitive Product 1 (CR-930), and Competitive Product 2 (ST-7028A) are shown in Table 1. Figure 5 .

[0162] 2. Comparison of light transmittance using a spectrophotometer: The oil-absorbing particles of Example 1-2, Comparative Example 1-2, and Competitor 1-2 were dissolved in anhydrous ethanol at a ratio of 1:2 to form a test slurry. The test slurry was scraped onto a glass sheet with a wire rod coater to a film thickness of 10 μm, and then the comparative light transmittance was detected using a spectrophotometer.

[0163] The wavelength is set at 400nm-780nm visible light.

[0164] The transmittance and haze are recorded in Table 2.

[0165] The detection situation of Example 1 is referenced Figure 6 , 7 .

[0166] Figure 6 The left side shows the oil-absorbing particles of Example 1 (indicated by the red arrow), and the right side shows the test slurry formed by dissolving Example 1 in anhydrous ethanol (indicated by the blue arrow).

[0167] Figure 7The left side shows the oil-absorbing particles of Example 1 being pushed onto a glass sheet using a wire rod coater, and the right side shows the test slurry of Example 1 being scraped to form a film.

[0168] Table 2

[0169]

[0170] According to the test data in Table 2, Examples 1-4 have excellent transparency, are not likely to leave obvious white marks on the hair, maintain the natural color and luster of the hair, and improve the overall aesthetics.

[0171] Test 3: Sun protection performance

[0172] The oil-absorbing particles of Example 1-2, Comparative Example 1-2, and Competitor 1 were tested using UV-2000 equipment according to the method of group standard T / GDICST002-2023, and the measured SPF values ​​and PA values ​​were recorded in Table 3.

[0173] Table 3

[0174] project spf PA value Example 1 7.32 ++ Example 2 7.06 ++ Comparative Example 1 3.05 + Comparative Example 2 3.89 + Competitor 1 1.60 0

[0175] According to the test data in Table 3, the oil-absorbing particles of Examples 1-2 do have good sun protection properties and can effectively protect hair from damage, thus truly achieving the function of protecting hair health from the source.

[0176] In summary, Comparative Example 1 increases the processing temperature of step 1 on the basis of Example 1, and Comparative Example 2 reduces the speed of step 1 on the basis of Example 1. These changes make it impossible for the HDI / trimethylol hexyl lactone crosslinked polymer to cooperate well with the hollow corn starch, affecting the special structure of the fluffy microspheres, resulting in poor effects. Therefore, it is necessary to strictly limit the raw materials, dosage and preparation method for preparing the fluffy microspheres in order to obtain a special structure and achieve unexpected excellent effects.

[0177] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A fluffy microsphere for dry hair spray, characterized in that: The raw materials include, by weight: 5-20 parts of hollow corn starch, 35-60 parts of HDI / trimethylol hexyl lactone cross-linked polymer, 0.1-5 parts of zinc oxide, and 1-10 parts of lauroyl lysine; The method for preparing the fluffy microspheres used in dry hair spray comprises the following steps: Step 1: Stir the hollow corn starch at 1000-2000 r / min and 60-80° C., spray the HDI / trimethylol hexyl lactone crosslinked polymer solution on the surface of the hollow corn starch, and keep stirring for 20-45 minutes to obtain the wrapped hollow corn starch; Step 2: maintaining 1000-2000r / min, setting the temperature to 85-95°C, spraying zinc oxide onto the wrapped hollow corn starch to make it adhere to the surface of the wrapped hollow corn starch to form a deposit, and continuously stirring for 20-45min to obtain deposited hollow corn starch; Step 3: Set the speed to 1500-2500 r / min, the temperature to 85-95° C., spray lauroyl lysine onto the deposited hollow corn starch, and continue stirring for 45-75 minutes to obtain fluffy microspheres for dry hair spray.

2. The fluffy microspheres for dry hair spray according to claim 1, characterized in that: The raw materials include the following in parts by mass: 10-15 parts of hollow corn starch, 45-50 parts of HDI / trimethylol hexyl lactone cross-linked polymer, 0.5-1.5 parts of zinc oxide, and 0.5-1.5 parts of lauroyl lysine.

3. The fluffy microspheres for dry hair spray according to claim 1, characterized in that: The particle size of the hollow corn starch is 2.5-4 μm.

4. The fluffy microspheres for dry hair spray according to claim 1, characterized in that: The particle size of the fluffy microspheres used in the dry hair spray is 4-8 μm.

5. A method for preparing fluffy microspheres for dry hair spray according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step 1: Stir the hollow corn starch at 1000-2000 r / min and 60-80° C., spray the HDI / trimethylol hexyl lactone crosslinked polymer solution on the surface of the hollow corn starch, and keep stirring for 20-45 minutes to obtain the wrapped hollow corn starch; Step 2: maintaining 1000-2000r / min, setting the temperature to 85-95°C, spraying zinc oxide onto the wrapped hollow corn starch to make it adhere to the surface of the wrapped hollow corn starch to form a deposit, and continuously stirring for 20-45min to obtain deposited hollow corn starch; Step 3: Set the speed to 1500-2500 r / min, the temperature to 85-95° C., spray lauroyl lysine onto the deposited hollow corn starch, and continue stirring for 45-75 minutes to obtain fluffy microspheres for dry hair spray.

6. The method for preparing fluffy microspheres for dry hair spray according to claim 5, characterized in that: The step 1 is carried out at 1500 r / min and 70° C.

7. The method for preparing fluffy microspheres for dry hair spray according to claim 5, characterized in that: In the step 1, the HDI / trimethylol hexyl lactone crosslinked polymer solution is sprayed in small amounts and multiple times.

8. An oil-absorbing particle, characterized in that: Including fluffy microspheres and silica used in dry hair spray; The fluffy microspheres for dry hair spray are the fluffy microspheres for dry hair spray according to any one of claims 1 to 4 or the fluffy microspheres for dry hair spray prepared according to the preparation method of the fluffy microspheres for dry hair spray according to any one of claims 5 to 7.

9. The oil absorbing particles according to claim 8, characterized in that: According to the mass fraction of the oil-absorbing particles, the fluffy microspheres used in the dry hair spray are 50-70 parts, and the silica is 30-50 parts.

Citation Information

Patent Citations

  • Deoiling fluffy washing-free hair drying spray and preparation method thereof

    CN114272156A

  • Wrapped starch microspheres and preparation method thereof

    CN114957731A

Cited By

  • Cosmetic plant powder containing active ingredients of whole peony plants as well as preparation method and application of cosmetic plant powder

    CN121360064A